Italian Fascism and Developmental Dictatorship - Gregor, A. James (Anthony James), 1929- (Book collections on Project MUSE., 1979)
Political scientists generally have been disposed to treat Italian Fascism--if not generic fascism--as an idiosyncratic episode in the special history of Europe. James Gregor contends, to the contrary, that Italian Fascism has much in common with an inclusive class of developmental revolutionary regimes. Originally published in 1980. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.